A consumer adoption model for personalized medicine: an exploratory study. Issue 4 (28th October 2014) - Hitz, Anja; Prevel Katsanis, Lea
Abstract : Purpose: – The purpose of this research is to identify factors linked to the potential acceptance of personalized medicine (PM) by consumers. Roger's diffusion of innovation model (1995) and the work of Duguay et al. (2003) on transgenic biopharmaceuticals contributed to the development of the proposed conceptual model. Design/methodology/approach: – The study design was an exploratory cross-sectional survey that used a Canadian national online panel of 307 respondents. Findings: – The results suggest that the most important factors leading to consumer adoption of PM are knowledge, relative advantage and compatibility with existing values. The level of homophilus traits was negatively related to the acceptance of PM. Originality/value: – Marketers will need to provide documented evidence of PM's benefits over existing therapy based on improved efficacy and reduced side effects. Further, concerns about higher price, product distribution and drug reimbursement policies may limit its acceptance. This is the first study to examine the potential adoption and acceptance of PM by consumers.